Biomechanical Evaluation of the TightRope Versus Traditional Docking Ulnar Collateral Ligament Reconstruction Technique: Kinematic and Failure Testing. (May 2013) - Lynch, Jamie L.; Maerz, Tristan; Kurdziel, Michael D.; Davidson, Abigail A.; Baker, Kevin C.; Anderson, Kyle
Background: Numerous variations of ulnar collateral ligament (UCL) reconstruction have been described since the original technique by Jobe et al. Purpose/Hypothesis: To biomechanically compare the new TightRope technique and the traditional ulnar bone tunnels as used in the docking technique. The hypothesis was that the TightRope technique would exhibit improved kinematics and comparable failure properties. Study Design: Controlled laboratory study. Methods: Seven matched pairs of cadaveric arms (mean age, 44.71 years) were tested in both the native state and reconstructed state. Kinematics were assessed at 15° to 90° of flexion by applying a 1.5-N·m valgus torque and measuring the resultant angular displacement. Failure testing was performed by loading to failure at 4.5 deg/s in 70° of flexion. Sides of a matched pair were randomized to the TightRope (TR) and docking (DO) techniques after testing the native state. Results: There was no significant difference in kinematic results between the native state and reconstructed state in either the TR or DO group at 15° to 75° of flexion. At 90°, the TR group had significantly higher angular displacement (2.23° ± 1.0°) compared with the native state (1.31° ± 0.7°) ( P = .020). The TR-reconstructed specimens had significantly lower initial stiffness (49.34 ± 19.3 N·m/rad vs 82.47 ± 36.0 N·m/rad, respectively; P = .007) and total stiffness (53.81 ± 27.8 N·m/rad vs 101.06 ± 34.4 N·m/rad, respectively; P < .001) than did the paired native specimens. In addition, the TR-reconstructed specimens had significantly lower torsional torque at 5° of valgus rotation (mean, 4.61 ± 2.2 N·m vs 7.62 ± 3.7 N·m, respectively; P = .010), at 15° of valgus rotation (12.24 ± 4.4 N·m vs 20.65 ± 6.8 N·m, respectively; P = .002), and at ultimate failure (19.18 ± 7.5 N·m vs 25.42 ± 7.1 N·m, respectively; P = .025) than did the paired native specimens. There was no significant difference in torsional torque between the TR and DO groups at 5° of valgus rotation (4.61 ± 2.2 N·m vs 4.09 ± 1.7 N·m, respectively; P = .644), at 15° of valgus rotation (12.24 ± 4.4 N·m vs 17.94 ± 7.23 N·m, respectively; P = .178), or at failure (19.18 ± 7.5 N·m vs 23.19 ± 10.6 N·m, respectively; P = .444). The DO group exhibited significantly higher angular displacement at failure than did the native state (28.12° ± 8.5° vs 18.04° ± 4.8°, respectively; P = .009), but there was no difference at 3 N·m of loading. There was no significant difference in angular displacement either at 3 N·m or at failure between the native state and reconstructed state in the TR group. Conclusion: Both the TR and DO techniques restored native joint kinematics from 15° to 75° of flexion under low loading conditions. While the TR technique exhibited inferior failure torque compared with the native state, the DO technique did not differ from the native state. No differences were found between the TR and DO groups when compared directly. The DO technique restored valgus stability under high loading to a greater extent than did the TR technique but also failed at higher angular displacement. Clinical Relevance: Strong postoperative UCL reconstruction fixation is important to restore ulnotrochlear joint stability. Our study demonstrates that the new TR technique has comparable kinematic and failure properties to the traditional DO technique.